2009
DOI: 10.1177/0969733009104609
|View full text |Cite
|
Sign up to set email alerts
|

The Struggle for Dignity by People with Severe Functional Disabilities

Abstract: The purpose of this study was to investigate what strategies people with severe functional disabilities who receive personal assistance in their homes use in their daily life to achieve autonomy, integrity, influence and participation. Qualitative interviews were carried out and subjected to qualitative latent content analysis. The main finding was expressed in terms of six subthemes: trying to keep a private sphere; striving to communicate; searching for possibilities; taking the initiative; striving to gain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 38 publications
1
33
0
Order By: Relevance
“…The security of having a limited number of people as assistants also contributes to increased satisfaction. These findings are in accordance with the family members’ relative with a disability which was included in a previous study by Wadensten and Ahlström (2009a). In that study several problems were associated with personal assistance but these were outweighed by the freedom of movement and security it gives.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The security of having a limited number of people as assistants also contributes to increased satisfaction. These findings are in accordance with the family members’ relative with a disability which was included in a previous study by Wadensten and Ahlström (2009a). In that study several problems were associated with personal assistance but these were outweighed by the freedom of movement and security it gives.…”
Section: Discussionsupporting
confidence: 89%
“…The study design was qualitative and descriptive, based on in‐depth interviews with family members. The study was part of a comprehensive project focusing on personal assistance and the life conditions of persons with severe neurological disease who were receiving personal assistance (Ahlström 2006, 2007, Ahlström & Wadensten 2009, Wadensten & Ahlström 2009a,b). Diagnoses and demographic characteristics of the person with a disability who received personal assistance are presented in previous papers (Ahlström 2006, 2007).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Results from such studies have shown that a good relationship is very important (Ahlstrom, 2006;Ahlstrom & Wadensten, 2009;Matsuda et al, 2005;Wadensten & Ahlstrom, 2009a;Wadensten & Ahlstrom, 2009b). Marquis and Jackson (2000) found that the interpersonal qualities of personal assistants are more important to the disabled person than their technical skills are.…”
Section: Discussionmentioning
confidence: 99%
“…Nurse researchers, in particular, have conducted a wide range of qualitative research studies engaging patients and professionals to develop in-depth perspectives and discussions regarding the meaning and implications dignity in care (43)(44)(45)(46)(47)(48)(49)(50)(56)(57)(58) . There has also been some quantitative work in this area (51) .…”
Section: Dignity and Nursing Ethics Researchmentioning
confidence: 99%